2022
DOI: 10.1200/jco.2022.40.28_suppl.389
|View full text |Cite
|
Sign up to set email alerts
|

Virtual care beyond COVID-19: Patient and physician perspectives.

Abstract: 389 Background: The COVID-19 pandemic catalyzed rapid implementation of virtual care (VC), resulting in new opportunities to integrate technology and a need to evaluate patient and provider experiences. To inform sustainment beyond COVID-19, we evaluated perceptions of VC at a comprehensive cancer centre in Toronto, Canada. Methods: Physicians who provided VC during the pandemic, and patients with a valid email address on file and at least one visit with centre in the preceding 12 months were eligible to part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Our cross-sectional survey demonstrated that overall, staff are satisfied with the current remote work paradigm and wish to 20 a large proportion of physician respondents indicated that they were concerned that virtual care detracts from the human interaction that they value as part of patient care. In addition, adequate onsite support for indirect patient care and administrative work was a concern for other professions with emphasis on the impact on efficiency and fairness in distribution of work.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Our cross-sectional survey demonstrated that overall, staff are satisfied with the current remote work paradigm and wish to 20 a large proportion of physician respondents indicated that they were concerned that virtual care detracts from the human interaction that they value as part of patient care. In addition, adequate onsite support for indirect patient care and administrative work was a concern for other professions with emphasis on the impact on efficiency and fairness in distribution of work.…”
Section: Discussionmentioning
confidence: 91%
“…It may reflect concerns of workers left behind with ensuring that there are adequate levels of staff on-site to provide support and direct patient care, and the actual experience with performing clinical work virtually. We did not evaluate the latter point explicitly in our survey, however, in another study focusing on virtual care specifically, 20 a large proportion of physician respondents indicated that they were concerned that virtual care detracts from the human interaction that they value as part of patient care. In addition, adequate on-site support for indirect patient care and administrative work was a concern for other professions with emphasis on the impact on efficiency and fairness in distribution of work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of 397 cancer patients receiving virtual care during the COVID‐19 pandemic in Alberta Canada, patients receiving follow‐up care were more satisfied with virtual care than those on treatment (83.6% vs. 73.2%, p < 0.05) 41 . Similarly, of 2343 patients and 100 physicians participating in the parent PM Virtual Care study, patients who recently completed treatment were two times more likely to prefer in‐person visits compared to those in long‐term (5 or more years) follow‐up 32 . Additionally, long‐term follow‐up care was selected by both patients and physicians as the most appropriate type of visit for virtual visits 32 .…”
Section: Discussionmentioning
confidence: 98%